2007
DOI: 10.1111/j.1365-294x.2007.03426.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of multiple paternity in the largest rookery of Mediterranean loggerhead sea turtles

Abstract: Mating systems are a central component in the evolution of animal life histories and in conservation genetics. The patterns of male reproductive skew and of paternal shares in batches of offspring, for example, affect genetic effective population size. A prominent characteristic of mating systems of sea turtles seem to be a considerable intra- and interspecific variability in the degree of polyandry. Because of the difficulty of observing the mating behaviour of sea turtles directly in the open sea, genetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 35 publications
3
66
1
5
Order By: Relevance
“…Many studies of marine turtles (Harry and Briscoe 1988, Parker et al 1996, FitzSimmons 1998, Bollmer et al 1999, Kichler et al 1999, Crim et al 2002, Hoekert et al 2002, Moore and Ball 2002, Ireland et al 2003, Lee and Hays 2004, Jensen et al 2006, Zbinden et al 2007 have demonstrated the clear presence of multiple paternity. However, there are few studies of mating systems of freshwater species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies of marine turtles (Harry and Briscoe 1988, Parker et al 1996, FitzSimmons 1998, Bollmer et al 1999, Kichler et al 1999, Crim et al 2002, Hoekert et al 2002, Moore and Ball 2002, Ireland et al 2003, Lee and Hays 2004, Jensen et al 2006, Zbinden et al 2007 have demonstrated the clear presence of multiple paternity. However, there are few studies of mating systems of freshwater species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mating systems of turtles have substantially advanced in the recent decades (Galbraith 1991, Galbraith et al 1993, Bowen and Karl 1996, Rieder 1996, Curtis 1998, FitzSimmons 1998, Crim et al 2002, Moore and Ball 2002, Jensen et al 2006, Zbinden et al 2007, Refsnider 2009, Theissinger et al 2009, Fantin et al 2010, Stewart and Dutton 2011, Lasala et al 2013, Todd et al 2013. However, the fact that the majority of species are aquatic behavior in nature and accounts for the lack of information for most species (Carpenter and Ferguson 1977).…”
Section: Introductionmentioning
confidence: 99%
“…However, some females might not be detected by foot patrols because they nest at a different time of the season (particularly at tropical sites with extended seasons) when monitoring effort is not in effect or they nest on beaches that are not patrolled at all. Consequently, it is broadly assumed that females lay 3 clutches on average, even though 5 or more clutches might occur at some sites (Zbinden et al 2007). Thus, current estimates of 2280−2787 and 339−360 adult female loggerhead and green turtles, respectively, nest each year in the Mediterranean (Broderick et al 2002, Casale & Margaritoulis 2010) might be major underestimates.…”
Section: Adult Femalesmentioning
confidence: 99%
“…For male leatherbacks, these adaptations may include the areas they select to intercept females prior to the nesting season. While all species of sea turtle exhibit polyandry (Kichler et al, 1999;Ireland et al, 2003;Jensen et al, 2006;Zbinden et al, 2007;Theissinger et al, 2009;Joseph and Shaw, 2011), multiple paternity in Atlantic leatherback clutches has been observed in low proportions (10-41.7%; Crim et al, 2002;Dutton, 2011, 2014;Figgener et al, 2016). Few instances of inter-nesting mating have been identified in leatherbacks (Figgener et al, 2016), and successive nests laid by most females reveal consistent paternities throughout the nesting season, indicative of sperm storage from mating event(s) occurring prior to the nesting season (Crim et al, 2002;Stewart and Dutton, 2011;Figgener et al, 2016).…”
Section: Inferred Mating Behaviormentioning
confidence: 99%